Numerical model of the ice cover evolution in Arctic Seas for the operational forecasting - S. V. Klyachkin; R. B. Guzenko; R. I. May (Лëд и снег, 2015)
The dynamic-thermodynamic model of the ice cover evolution is used for operational 5‑day ice forecasts in the Russian Arctic seas and to obtain some statistical estimates of the ice cover state. The model is a numerical realization of the heat budget and the motion balance equations for sea and ice cover with appropriate boundary conditions. The statistical processing of the data resulted in revealing characteristics of seasonal and spatial variability of the ice compressionin the Barents and Kara Seas.